2020
DOI: 10.1111/fwb.13528
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal variation in global range‐size of aquatic macrophyte species shows evidence for a Rapoport effect

Abstract: 1. To test hypotheses concerning the applicability of the Rapoport effect (RE: "species that occur at higher latitudes tend to have greater geographical range-size than species which have ranges limited to latitudes closer to the equator") to aquatic macrophytes at global scale, we analysed the world latitudinal distribu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 86 publications
0
37
0
Order By: Relevance
“…Based on a previous study on global variation in community similarity of lake plants (Alahuhta et al, 2017), we also expected (H2) that within–ecoregion and across–ecoregion heterogeneity would be caused by species replacements rather than by differences in species richness. Similarly, we predicted (H3) that climatic forcing would explain a great deal of variation in the robustness of freshwater plant ecoregions (Heino, 2011; Chappuis et al, 2012; Alahuhta et al, 2021, 2020; García–Girón et al, 2020a, 2020b), with topography, Pleistocene Ice Age legacies, human footprint, water alkalinity, availability of inland waterbodies and the surface area of individual regions playing an important supplementary role (Lacoul & Freedman, 2006; Chappuis et al, 2014; Iversen et al, 2019; Murphy et al, 2019, 2020). Finally, we hypothesised (H4) that ecoregions would be a more robust and useful classification for floating–leaved and submerged plants.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…Based on a previous study on global variation in community similarity of lake plants (Alahuhta et al, 2017), we also expected (H2) that within–ecoregion and across–ecoregion heterogeneity would be caused by species replacements rather than by differences in species richness. Similarly, we predicted (H3) that climatic forcing would explain a great deal of variation in the robustness of freshwater plant ecoregions (Heino, 2011; Chappuis et al, 2012; Alahuhta et al, 2021, 2020; García–Girón et al, 2020a, 2020b), with topography, Pleistocene Ice Age legacies, human footprint, water alkalinity, availability of inland waterbodies and the surface area of individual regions playing an important supplementary role (Lacoul & Freedman, 2006; Chappuis et al, 2014; Iversen et al, 2019; Murphy et al, 2019, 2020). Finally, we hypothesised (H4) that ecoregions would be a more robust and useful classification for floating–leaved and submerged plants.…”
Section: Introductionmentioning
confidence: 74%
“…Unexpectedly, species replacement and richness difference explained equal amount of variation for ecoregion robustness. Recent studies have clearly shown that species replacement primarily structures freshwater plants independent of spatial scale and study region (Alahuhta et al, 2017; Murphy et al, 2020; Alahuhta et al, 2021). However, these previous exercises utilised an alternative measure of richness difference (i.e., nestedness), which does not consider overall difference in species richness explicitly (Legendre 2014; Schmera et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mean, median and standard deviation for climate variables per gridcell were obtained using a 10°g ridcell shapefile and the Zonal statistics tool in QGIS (version 3.4.9-Madeira). The area occupied by each agricultural land use category (and subsequently total agricultural land cover) per gridcell was obtained using the above-mentioned shapefile and the Zonal Histogram tool in the ArcMap Spatial Analyst toolbox using ArcMap v. 9.3.1, see Murphy et al (2019Murphy et al ( , 2020 for further details. All-species richness and ecozone-endemic species richness values were obtained from Murphy et al (2019).…”
Section: Spatial Environmental and Landscape Variablesmentioning
confidence: 99%